URGENSI KESIAPAN GURU DAN SEKOLAH TERHADAP PENERAPAN KURIKULUM MERDEKA BELAJAR DI SEKOLAH DASAR - Ayyesha Dara Fayola; Ratih Rahmawati (Adisam Publisher, 2024)
The Merdeka Program, as an alternative program to overcome the decline in the quality of learning during the pandemic, provides